2023
DOI: 10.3389/fphar.2023.1155163
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of guggulsterone by modulating apoptotic markers: a systematic review and meta-analysis

Abstract: Background: Guggulsterone (pregna-4,17-diene-3,16-dione; C21H28O2) is an effective phytosterol isolated from the gum resin of the tree Commiphora wightii (Family Burseraceae) and is responsible for many of the properties of guggul. This plant is widely used as traditional medicine in Ayurveda and Unani system of medicine. It exhibits several pharmacological activities, such as anti-inflammatory, analgesic, antibacterial, anti-septic and anticancer. In this article, the activities of Guggulsterone against cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Natural products and herbal antioxidants have gained the attention of researchers due to their hepatoprotective nature and efficacy in protecting against DILI (Gupta et al, 2023;Khan et al, 2023;Singh, Gupta, Sarwat, & Siddique, 2022;Singh, Khan, Akhtar, Rehman, et al, 2022). Studies have reported that natural products rich in flavonoids, polysaccharides, terpenes, triterpenes, polyphenols, and alkaloids have hepatoprotective effects against DILI (Figure 3) (Farghali et al, 2015).…”
Section: Protecting the Liver: Potential Of Natural Products As Agent...mentioning
confidence: 99%
“…Natural products and herbal antioxidants have gained the attention of researchers due to their hepatoprotective nature and efficacy in protecting against DILI (Gupta et al, 2023;Khan et al, 2023;Singh, Gupta, Sarwat, & Siddique, 2022;Singh, Khan, Akhtar, Rehman, et al, 2022). Studies have reported that natural products rich in flavonoids, polysaccharides, terpenes, triterpenes, polyphenols, and alkaloids have hepatoprotective effects against DILI (Figure 3) (Farghali et al, 2015).…”
Section: Protecting the Liver: Potential Of Natural Products As Agent...mentioning
confidence: 99%
“…Various pathways may contribute to breast carcinogenesis, with overactivation of NF-κB signaling widely reported; NF-κB controls the expression of several antiapoptotic genes crucial for carcinogenesis (Pavitra et al, 2023). GS treatment of cancer cells suppresses the expression of antiapoptotic genes, NF-κB, and genes responsible for inflammation and cancer metastasis (Gupta et al, 2023). Cancer cells exposed to radiation normally activate prosurvival signaling pathways to prevent apoptotic cell death and according to the studies, ionizing radiation has been shown to stimulate NF-κB and related pathways which are vital for the survival and propagation of cancer cells (Huang & Zhou, 2020).…”
Section: Breast Cancermentioning
confidence: 99%
“…GS has been evaluated for toxicity using both in vitro and animal models. In vitro studies generally indicate that GS is nontoxic up to concentrations of 50 μM across various cell lines; at higher concentrations, specifically above 100 μM, it has been observed to induce apoptosis in certain cancer cell lines (Gupta et al, 2023) chronic toxicity studies in rodents have shown that long-term administration of GS at a dose of 500 mg/kg/day did not result in significant organ damage, although there were mild elevations in hepatic enzymes (Preethi et al, 2021). Studies reported that adverse effects are generally rare but can include mild gastrointestinal issues and skin rashes at high doses; there are isolated reports of elevated liver enzymes, although these findings have not been confirmed in larger clinical trials (Preethi et al, 2021).…”
Section: Toxicity and Safety Datamentioning
confidence: 99%